2007
DOI: 10.1074/jbc.m701626200
|View full text |Cite
|
Sign up to set email alerts
|

Defining Paxilline Biosynthesis in Penicillium paxilli

Abstract: Indole diterpenes are a large, structurally and functionally diverse group of secondary metabolites produced by filamentous fungi. Biosynthetic schemes have been proposed for these metabolites but until recently none of the proposed steps had been validated by biochemical or genetic studies. Using Penicillium paxilli as a model experimental system to study indole diterpene biosynthesis we previously showed by deletion analysis that a cluster of seven genes is required for paxilline biosynthesis. Two of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…paxQ -containing transformants converted 13-desoxypaxilline into paxilline. These results confirmed that paspaline, β-PC-M6 and 13-desoxypaxilline are paxilline intermediates and that paspaline and β-PC-M6 are substrates for PaxP, and 13-desoxypaxilline is a substrate for PaxQ [10]. Stepwise introduction of the pax genes into A. oryzae showed that addition of paxG-C-M-B-P-Q was sufficient to reconstitute the machinery for paxilline biosynthesis [12].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…paxQ -containing transformants converted 13-desoxypaxilline into paxilline. These results confirmed that paspaline, β-PC-M6 and 13-desoxypaxilline are paxilline intermediates and that paspaline and β-PC-M6 are substrates for PaxP, and 13-desoxypaxilline is a substrate for PaxQ [10]. Stepwise introduction of the pax genes into A. oryzae showed that addition of paxG-C-M-B-P-Q was sufficient to reconstitute the machinery for paxilline biosynthesis [12].…”
Section: Introductionmentioning
confidence: 63%
“…While deletion mutants of paxP and paxQ were blocked for paxilline biosynthesis, they accumulated paspaline and 13-desoxypaxilline, respectively, confirming that both genes were required for paxilline biosynthesis and that paspaline and 13-desoxypaxilline were the most likely substrates for the corresponding enzymes [9]. This was confirmed by feeding these compounds to strains lacking the pax cluster but containing ectopically integrated copies of paxP and paxQ [10]. Transformants containing paxP converted paspaline into 13-desoxypaxilline as the major product and β-PC-M6 as the minor product.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In other works, Tagami et al (2013) successfully synthesised the indole-diterpene paxilline (21) in A. oryzae , a bioactive natural product that shows MRSA growth inhibition. Six genes had first been identified as being involved in biosynthesis of paxilline in the native producer Penicillium paxilli (Saikia et al 2006, 2007) and were expressed heterologously by Tagami et al (2013). Also in this case, the authors adopted a stepwise transformation approach and were therefore able to isolate and identify the intermediate compounds of the paxilline biosynthetic pathway.…”
Section: Heterologous Expression In Filamentous Fungimentioning
confidence: 99%